Forecasting economic stability (at the small Ukrainian construction companies) - Stetsenko, S.; Bielienkov, А.; Antropov, Y. (Ways to Improve Construction Efficiency, 2018)
Application of discriminant analysis helped identify the key factors that can help you with a high degree of probability to predict the problems of finance of small construction company. An appropriate model.